1987
DOI: 10.1161/01.str.18.6.1031
|View full text |Cite
|
Sign up to set email alerts
|

Carotid restenosis: long-term noninvasive follow-up after carotid endarterectomy.

Abstract: Recurrent stenosis has not been a primary consideration in the selection of patients for carotid endarterectomy. We have studied the incidence of postoperative restenosis retrospectively in 265 patients following 310 carotid endarterectomies. Two hundred fourteen patients (248 endarterectomies) were examined at 6-12 month intervals using ocular pneumopiethysmography, spectral analysis, and B-mode imaging. The absolute incidence of recurrent carotid disease was 28% (69 of 248), with a 13% (33 of 248) incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 10 publications
2
43
0
2
Order By: Relevance
“…Other observational studies or smaller clinical trials have reported variable rates of restenosis after CEA. [364][365][366][367][368][369] Imaging technique, length of follow-up, stenosis criterion, loss rates, and case mix undoubtedly contribute to these disparate findings. According to a recent narrative review, however, the rate of hemodynamically significant restenosis after CEA is probably 5% to 7% during variable periods of follow-up.…”
Section: Follow-up Imaging and Restenosis After Extracranial Carotid mentioning
confidence: 99%
“…Other observational studies or smaller clinical trials have reported variable rates of restenosis after CEA. [364][365][366][367][368][369] Imaging technique, length of follow-up, stenosis criterion, loss rates, and case mix undoubtedly contribute to these disparate findings. According to a recent narrative review, however, the rate of hemodynamically significant restenosis after CEA is probably 5% to 7% during variable periods of follow-up.…”
Section: Follow-up Imaging and Restenosis After Extracranial Carotid mentioning
confidence: 99%
“…407,440,468,624,625,628 -630 When periodic duplex scanning is used, hemodynamically significant recurrent stenosis rates of 5% to 7% have been reported in multicenter trials in which the quality of surgery is monitored carefully. 396,403,404,406,440,628,[631][632][633][634][635][636][637][638][639][640][641][642][643][644][645] Recurrent carotid stenosis after CEA is a trimodal phenomenon. The first event is not really recurrence but instead represents an unsatisfactory or incomplete CEA.…”
Section: Anatomic Durability Of Carotid Surgery and Carotid Stentingmentioning
confidence: 99%
“…3 Although the majority (95.4%) of patients remained asymptomatic in the follow-up period, the risk of Ͼ60% restenosis or occlusion in the present study (5/20 patients, 25%) is higher than reported for the 3 to 18 months of follow-up of the 645 patients in the surgical arm of the Asymptomatic Carotid Atherosclerosis Study (ACAS) (7.6% to 11.4%) 22 and greater than the 6-to 12-month rate reported in other series (8%). 23 Since the original goal of the procedure was stroke prevention, the current management was effective in 4 of the 5 patients with Ͼ60% restenosis or occlusion for the limited length of follow-up. However, even if one were to consider only restenosis of Ͼ80% as clinically warranting retreatment, the rate in the present study remains significant at 15% (3/20 patients).…”
Section: Discussionmentioning
confidence: 99%